Repeated Clinical Assessment Using Sensory Modality Assessment and Rehabilitation Technique for Diagnosis in Prolonged Disorders of Consciousness - da Conceição Teixeira, Liliana; Blacker, Danielle; Campos, Carlos; Garrett, Carolina; Duport, Sophie; Rocha, Nuno Barbosa (Frontiers in Human Neuroscience, 2021)
Purpose: The recommended way to assess consciousness in prolonged disorders of consciousness is to observe the patient’s responses to sensory stimulation. Multiple assessment sessions have to be completed in order to reach a correct diagnosis. There is however a lack of data on how many sessions are sufficient for validity and reliability. The aim of this study was to identify the number of Sensory Modality Assessment and Rehabilitation Technique (SMART) assessment sessions needed to reach a reliable diagnosis. A secondary objective was to identify which sensory stimulation modalities are more useful to reach a diagnosis. Materials and methods: A retrospective analysis of all the adult patients (who received a SMART assessment) admitted to a specialist brain injury unit over the course of four years was conducted (n=35). An independent rater analysed the SMART levels for each modality and session and provided a suggestive diagnosis based on the highest SMART level per session. Results: For the vast majority of patients between 5-6 sessions was sufficient to reach the final clinical diagnosis. The visual, auditory, tactile and motor function modalities were found to be more associated with the final diagnosis than the olfactory and gustatory modalities. Conclusions: These findings provide for the first time a rationale for optimising the time spent on assessing patients using SMART.